"Knowledge, clinical experience, and perceived need for training regarding molar-incisor hypomineralization among a group of Egyptian dental students: a cross-sectional study" - Alaa Mohammed Yehia; Amr M. Abdelaziz; Amira Badran (BMC, 2022)
Abstract Background Molar-Incisor Hypomineralization (MIH) is a common oral health condition that can lead to difficulties and complications for both dental professionals and patients. It also has a negative impact on the oral health-related quality of life. The present study aimed to assess the knowledge, clinical experience, and perceived need for training of a group of Egyptian dental students regarding MIH. Methods Paper-based survey administration method was used to collect the responses of dental students regarding their knowledge, clinical experience, and perceived need for training about MIH. The survey consisted of two sections of questions regarding clinical features, etiological factors, prevalence, materials used in treating these teeth, factors affecting the choice of restorative materials, and their preferences regarding clinical training of MIH. Descriptive statistics was used for the data analysis by using SPSS® Statistics Version 26. Results About two-thirds of the respondents were familiar with MIH (69.2%). The vast majority of students (87.8%) had difficulty distinguishing MIH as a developmental defect that differs from other tooth conditions (p < 0.001); most commonly enamel hypoplasia. The most common defects seen by the respondents were yellow/brown opacities (59.1%). Nearly half of the students (45.2%) choose composite resin as the material of choice for the treatment of MIH-affected teeth with aesthetics being the most common factor affecting the selection of restorative material. Almost all students expressed their needs for further clinical training on MIH, especially on treatment aspects. Conclusions Most students are familiar with MIH theoretically. However, there is an urgent need to include clinical training on MIH diagnosis in the practical sessions of pediatric dentistry courses.